Gullain Barre Syndrome: Acute Motor Axonal Neuropathy - Muralidhar, Shilpashree Bettadapura; Basavaraju, Chinthana Handankere; Hiremath, Shivalingayya Gadagayya; Venkatesh, Prashanth; Siddappa, Usha Dhoddametikurke; Suresh, Mandara Mathighatta (Journal of Neonatal Surgery, 2025)
BACKGROUND Guillain-Barré Syndrome (GBS) is an acute immune-mediated polyneuropathy that results in ascending paralysis, autonomic dysfunction, and neuromuscular impairment. OBJECTIVES This case highlights the presentation, diagnosis, and therapeutic management of Acute Motor Axonal Neuropathy (AMAN), a severe GBS variant. MATERIAL AND METHODS: A 73-year-old male patient case report, Cerebrospinal fluid (CSF) analysis showed mild pleocytosis with albuminocytologic dissociation, and MRI findings revealed an incidental posterior fossa arachnoid cyst. RESULT A 73-year-old male presented with gait ataxia, progressive limb weakness, and numbness. Cerebrospinal fluid (CSF) analysis showed mild pleocytosis with albuminocytologic dissociation, and MRI findings revealed an incidental posterior fossa arachnoid cyst. The patient underwent plasmapheresis (five cycles) along with neuro-rehabilitative therapy to remove pathogenic circulating autoantibodies and enhance recovery. Following plasmapheresis and physiotherapy, the patient demonstrated substantial neurological improvement, with restored motor function, preserved bulbar reflexes, and safe oral intake. CONCLUSION The critical role of early immunomodulatory intervention, particularly plasmapheresis and rehabilitation, in managing GBS variants like AMAN. Multidisciplinary care, close outpatient monitoring, and structured rehabilitative support are essential in optimizing functional outcomes and minimizing recurrence risks.